Advances in Minimally Invasive Surgery - Sanna, Andrea (IntechOpen, 2022)
The minimally invasive approach in medicine is one of the most common areas of interest in surgery.Advances in Minimally Invasive Surgery describes the latest trends, indications, techniques, and approaches in minimally invasive surgery. It provides step-by-step instructions for both routine and diagnostic procedures via illustrations and video collection.